Rhinolithiasis: A Misleading Entity. (September 2018) - Adib, Hayat; Natout, Mohamad Ali El; Zaytoun, Georges; Hadi, Usamah Al
Introduction: Rhinolithiasis is a rare entity; it entails a stone located in the nasal cavity. The entity presents with different signs and symptoms that can be easily confused with other more common clinical entities such as chronic rhinosinusitis. However, it can also mimic sinonasal tumors, making its proper diagnosis crucial. Materials and Methods: In this article, we present a case series of 15 patients over the past 13 years between 2002 and 2015 who were seen in the clinics at the American University of Beirut Medical Center. We will shed light on the common presenting symptoms, physical examination findings, proper diagnostic modalities, and treatment options. Our data will be compared to the literature. Conclusion: Rhinolithiasis could present with a wide spectrum of signs and symptoms and could be overlooked or mistaken for other diagnosis such as sinusitis or malignancy. It could be differentiated from other entities by rigid nasal endoscopy and computed tomography scan. The diagnosis of rhinolithiasis requires a high index of suspicion.